Metagenomic Characterization of the Human Intestinal Microbiota in Fecal Samples from STEC-Infected Patients - Gigliucci, Federica; von Meijenfeldt, F. A. Bastiaan; Knijn, Arnold; Michelacci, Valeria; Scavia, Gaia; Minelli, Fabio; Dutilh, Bas E.; Ahmad, Hamideh M.; Raangs, Gerwin C.; Friedrich, Alex W.; Rossen, John W. A.; Morabito, Stefano (Frontiers in Cellular and Infection Microbiology, 2018)
The human intestinal microbiota is a homeostatic ecosystem with a remarkable impact on human health and the disruption of this equilibrium leads to an increased susceptibility to infection by numerous pathogens. In this study, we used shotgun metagenomic sequencing and two different bioinformatics approaches, based on mapping of the reads onto databases and on the reconstruction of putative draft genomes, to investigate possible changes in the composition of the intestinal microbiota in samples from patients with Shiga Toxin-producing E. coli (STEC) infection compared to healthy and healed controls, collected during an outbreak caused by a STEC O26:H11 infection. Both the bioinformatic procedures used, produced similar result with a good resolution of the taxonomic profiles of the specimens. The stool samples collected from the STEC infected patients showed a lower abundance of the members of Bifidobacteriales and Clostridiales orders in comparison to controls where those microorganisms predominated. These differences seemed to correlate with the STEC infection although a flexion in the relative abundance of the Bifidobacterium genus, part of the Bifidobacteriales order, was observed also in samples from Crohn’s disease patients, displaying a STEC-unrelated dysbiosis. The metagenomics also allowed to identify in the STEC positive samples, all the virulence traits present in the genomes of the STEC O26 that caused the outbreak as assessed through isolation of the epidemic strain and whole genome sequencing. The results shown represent a first evidence of the changes occurring in the intestinal microbiota of children in the course of STEC infection and indicate that metagenomics may be a promising tool for the culture-independent clinical diagnosis of the infection.